2023
DOI: 10.1590/1678-4499.20220198
|View full text |Cite
|
Sign up to set email alerts
|

Analytical approach to relate evapotranspiration, canopyatmosphere coupling level, and water deficit sensitivity

Abstract: The decoupling factor (Ω) reflects the leading mechanisms responsible for canopy transpiration and allows to know the relevance of the control of stomatal or canopy conductance on transpiration (T). The Ω is strongly dependent on water availability and can be a good approach to describe how plants minimize excessive water loss by increasing the dominance of biotic factors that controls evapotranspiration under water deficit conditions. We provided an overview of how the Ω concept can be broadly used and applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
(164 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have shown that as Ω decreased, the linear regression correlation between g a and g c increased, indicating a stronger coupling effect between the canopy and atmosphere (Jiao et al, 2018; Zhang et al, 2016). Ω is a vital signal to evaluate the coupling degree between canopy and atmosphere, and the closer Ω is to 0, the more sensitive stomatal behaviour is to atmospheric environmental factors (Maldonado & Marin, 2023). Smaller decoupling coefficients indicate that transpiration rates are more influenced by VPD than R n , while larger Ω suggests the opposite (Fu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that as Ω decreased, the linear regression correlation between g a and g c increased, indicating a stronger coupling effect between the canopy and atmosphere (Jiao et al, 2018; Zhang et al, 2016). Ω is a vital signal to evaluate the coupling degree between canopy and atmosphere, and the closer Ω is to 0, the more sensitive stomatal behaviour is to atmospheric environmental factors (Maldonado & Marin, 2023). Smaller decoupling coefficients indicate that transpiration rates are more influenced by VPD than R n , while larger Ω suggests the opposite (Fu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The lowest values (omega ~ 0.6) were also observed mainly in the vegetative and tuber bulking stages. These lower Ω values are indicative that ET and GPP were mainly controlled by VPD and Rc (Aires et al, 2008;Jarvis and Mcnaughton, 1986;Martinez Maldonado and Marin, 2023;Nassif et al, 2014) under rainfed conditions of the RF site. Both omega and the correlation coefficient (r) had a similar trend of variation along crop growth.…”
Section: Et-gpp Coupling and The Omega Rolementioning
confidence: 94%
“…The high Ra between leaf surfaces and the air above the canopy indicates a lower diffusivity of water vapor from the leaves that makes ET more strongly controlled by incoming radiation and less dependent on stomatal conductance and canopy resistance (Jarvis, 1985;Jarvis and Mcnaughton, 1986;McNaughton and Jarvis, 1991;Steduto and Hsiao, 1998;Sutherlin et al, 2019a;Zhang et al, 2016). This omega Ω→1 gives to potato canopy a greater advantage because the transpiration is not affected by the stomatal conductance and the water fluctuations in the soil (Sutherlin et al 2019b;Martinez Maldonado and Marin 2023). As a result of tightly coupled carbon and water fluxes, and no canopy resistance restrictions for fluxes potato ecosystem became more efficient in increasing its capacity to optimize carbon gains to water losses as the crop growth progressed (Katul et al 2010b), a situation observed in the daily pattern of IWUE being strongly influenced by the LAI and the growth stages (Beer et al 2009).…”
Section: Et-gpp Coupling and The Omega Rolementioning
confidence: 99%